POTENTIAL FOR REPLACEMENT OF PORTLAND CEMENT BY CERAMIC RESIDUE IN THE SOIL-CEMENT MIXTURE FOR APPLICATION IN PAVING LAYER - Albino de Sousa, André; Santos da Silva, Cinthya; Arruda dos Santos, Robson; Amador de Abreu, Alexandra; de Souza Dias, Leonardo (Journal of Interdisciplinary Debates, 2021)
In 2018, of a total extension of 87,563 kilometers of road network, only 34.2% of the total presented satisfactory conditions to users. One of the main reasons for this scenario is linked to the high cost of maintenance, including the need for soil stabilization, since the composition of the pavement layers is directly linked to its resistance and durability. In this scenario, the chemical stabilization technique with soil-cement emerges as an alternative for using the soil, which initially did not present corresponding parameters for the respective use. However, the growing demand for replacement of Portland Cement in engineering services, due to the carbon dioxide levels released into the atmosphere during its production, has supported research that deals with the substitution of binder by waste generated by the production sectors, namely, red ceramic waste from the ceramic block industry. This research aims to evaluate the carrying capacity of soils stabilized with cement and the partial replacement by red ceramic waste. Soil characterization tests were carried out, which provided parameters for the dosage of the materials, and subsequent performance of the compaction, expansion and penetration tests. Based on the need to stabilize the soil classified as clayey, group A-7-6, and susceptible to great variation in volume, the addition of 13% by weight of Portland Cement to the mixture was evaluated and subsequent replacement of the binder in percentages of 20 and 30%. The results demonstrated a reduction in specific mass by increasing the substitution by RCR (Red Ceramic Residue), and also for the expansion presented by the compounds. The CBR test evaluated the percentage of 20% replacement as the one with the highest load capacity. For paving purposes both percentages of substitution analyzed are within the parameters that satisfy their respective uses in sub-base layers of flexible pavement.